Original papers Psychological stress and transepidermal water loss in atopic dermatitis: preliminary results - Kepska, Anna; Haftek, Marek; Nosbaum, Audrey; Pralong, Pauline; Nicolas, Jean-Francois; Berard, Frederic; Ograczyk, Alicja; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Atopic dermatitis (AD) is an inflammatory skin disease in which activation of specific T cells directed towards environmental allergens plays an important role. Environmental allergens’ penetration through the skin is facilitated by the skin barrier impairment what causes xerosis and transepidermal water loss (TEWL) increase. As AD is a chronic disease, there are many factors responsible for exacerbations during the course of the disease, including environmental stress. Aim : Evaluation of the correlation between the level of psychological stress and epidermal barrier function in AD patients. Material and methods: Eight AD patients were included in the study during which two consultations were performed in one month’s time. During each visit patients completed psychological questionnaires and had TEWL of uninvolved skin measured. The TEWL was also evaluated before and after the educational session which took place during the first visit. Results : The study did not show any statistically significant correlation between the level of psychological stress, epidermal barrier function (measured by TEWL) and AD severity both at the beginning of the study (before and after the educational session) and a month later (all p > 0.05). Conclusions : Negative observations could result from a small number of participants and a short follow-up period. However, consecutive studies excluding these limitations may play an important role in understanding the influence of stress on the skin barrier in atopic dermatitis and have reliable clinical implications.